Revitalising STEM Education: Can Culturo-Techno-Contextual Approach Help to Improve Students' Achievement and Problem-solving Skills in Chemistry? - Ademola, Ibukunolu A.; Owolabi, Tunde; Oladejo, Adekunle I.; Ogundajo, Lanre; Agbanimu, Deborah O.; Peter, Esther O.; Ogonenwe, John I.; Franklin, Onowugbeda U. (Journal of Educational Sciences, 2025)
This examined the effect of Culturo-Techno-Contextual Approach (CTCA) on students’ achievement and problem-solving skills in chemistry. It also captured gender influence as well as interaction effect of method and gender on achievement and problem-solving skills. The study employed mixed methods research design involving the collection of both quantitative and qualitative data. The sample size for the quasi-experimental phase of the study was 102 senior secondary II students selected from three senior secondary schools out of the 14 public and seven private schools. The experimental group comprised 53 students, while the control group consists of 53 students. Difficult Concept in Chemistry Questionnaire was used for the descriptive phase while Nuclear Chemistry Achievement Test, Nuclear Chemistry Problem-solving Skills Test and Nuclear Chemistry Students Interview Guide were used for the experimental phase of the study. Findings revealed a statistically significant effect of CTCA on students’ achievement [F(1,98) = 11.10; p < 0.05] and problem-solving skill [F(1,98) = 54.52; p < 0.05] but no statistically significant influence of gender on students’ achievement using CTCA [F (1,50) = .07; p > 0.05]. It was recommended that CTCA should be adopted as a method of teaching chemistry globally.